Robust fluorescent labelling of micropipettes for use in fluorescence microscopy: application to the observation of a mosquito borne parasite infection - BALABAN, AMANDA E. (J Microsc, 2017)
The ability to monitor micropipette injections with a high-resolution fluorescent microscope has utility for a variety of applications. Herein, different approaches were tested for creating broad-band fluorescently labelled glass micropipettes including: UV cured glass glues, baked glass enamel containing fluorescent dyes as well as nanodiamonds attached during pipette formation in the microforge. The most robust and simplest approach was to use labelled baked enamel on the exterior of the pipette. This approach was tested using pipettes designed to mimic a mosquito proboscis for the injection of the malaria parasite, Plasmodium spp., into the dermis of a living mouse ear. The pipette (~30 micron diameter) was easily detected in the microscopy field of view and tolerated multiple insertions through the skin. This simple inexpensive approach to fluorescently labelling micropipettes will aid in the development of procedures under the fluorescent microscope.